PRIVATE INTERNATIONAL LEGAL EDUCATION AND ITS RELEVANCE IN A EUROPEAN CONTEXT (EU and comparative law issues and challenges series (ECLIC), 2019)
At the request of the European Parliament’s Committee on Legal Affairs (JURI Committee), the European Parliament’s Policy Department for Citizens’ Rights and Constitutional Affairs issued a study titled “Building Competence in Commercial Law in the Member States”1, aimed at shedding light on cross-border commercial contracts and their operation in theory and practice, mainly within European Union Member States. Most of the measures analysed and proposed for building competence in commercial law, despite the title of the study not being explicit in the matter, are cross-border measures, and thus of private international law. The last proposal of the study is the improvement of legal education in the field of private international law. The present paper aims to assess the level of the Romanian legal system and its compatibility with the measures proposed in the above-mentioned study, while focusing, throughout, on the role of legal education. Is improving private international legal education the final (least important) measure to be taken? Can legal education in the member states be improved on a E.U. level, and if so, how? These are just some of the issues that the present paper looks to tackle.